SOCIO-ECONOMIC IMPACT OF THE MARITIME EDUCATION UPGRADING PROGRAM - Ochavillo, Gregorio S. (PEOPLE: International Journal of Social Sciences, 2016)
This study endeavored to determine the impact of the Maritime Education Upgrading Program of PIT-KVNR on the socio-economic status of its graduates from school years 2002-2003 to 2007-2008. A descriptive-comparative approach design was used with two groups of respondents and total sample size of 296. It was found out that, before these graduates entered the program, the socio-economic status between parents of the two groups of marine transportation graduates-respondents were already significantly different, while there was no significant difference in the socio-economic status between parents of the two groups of marine engineering graduates-respondents. Furthermore, there were significant differences between groups of marine transportation and marine engineering graduates-respondents on their socio-economic status after they graduated from the program. Moreover, results revealed that the socio-economic status of graduates from all groups of respondents have greatly improved over a short span of time after they graduated from the program. On the other hand, the respondents from both groups also accounted the extent of performance of the Maritime Education Upgrading Program as providing opportunities for the respondents to achieve performance ranging from higher to highest level.